2020
DOI: 10.48550/arxiv.2003.09188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of pre-biotic molecules containing Peptide-like bond in a hot molecular core, G10.47+0.03

Prasanta Gorai,
Bratati Bhat,
Milan Sil
et al.

Abstract: After hydrogen, oxygen, and carbon, nitrogen is one of the most chemically active species in the interstellar medium (ISM). Nitrogen bearing molecules have great importance as they are actively involved in the formation of biomolecules. Therefore, it is essential to look for nitrogen-bearing species in various astrophysical sources, specifically around high-mass star-forming regions where the evolutionary history is comparatively poorly understood. In this paper, we report observation of three potential pre-bi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Detailed chemical modeling has been carried out to study the abundances of the species observed in G31. Our Chemical Model for Molecular Cloud (CMMC) (Das et al, 2015a(Das et al, ,b, 2016Gorai et al, 2017a,b;Sil et al, 2018;Gorai et al, 2020;Sil et al, 2021;Das et al, 2021) is considered for this modeling. 2013) and infall velocity variation is derived from the Equation 1 by using v 1000 = 4.9 km s −1 .…”
Section: Chemical Modelingmentioning
confidence: 99%
See 4 more Smart Citations
“…Detailed chemical modeling has been carried out to study the abundances of the species observed in G31. Our Chemical Model for Molecular Cloud (CMMC) (Das et al, 2015a(Das et al, ,b, 2016Gorai et al, 2017a,b;Sil et al, 2018;Gorai et al, 2020;Sil et al, 2021;Das et al, 2021) is considered for this modeling. 2013) and infall velocity variation is derived from the Equation 1 by using v 1000 = 4.9 km s −1 .…”
Section: Chemical Modelingmentioning
confidence: 99%
“…The time evolution of the physical parameters (H 2 density and temperature) are considered in three significant steps: isothermal collapsing phase, warm-up phase, and post-warmup phase. This type of straightforward model is best suited to study the chemical evolution of hot cores (Gorai et al, 2020;Sil et al, 2021). As discussed in Section 2.2, the gas cloud envelope is divided into 23 spherical shells.…”
Section: Chemical Modelingmentioning
confidence: 99%
See 3 more Smart Citations